2004
DOI: 10.4315/0362-028x-67.11.2500
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Studies on Listeria in Smoked Fish Plants: Impact of Intervention Strategies on Contamination Patterns

Abstract: Four ready-to-eat smoked fish plants were monitored for 2 years to study Listeria contamination patterns and the impact of plant-specific Listeria control strategies, including employee training and targeted sanitation procedures, on Listeria contamination patterns. Samples from the processing plant environment and from raw and finished product were collected monthly and tested for Listeria spp. and Listeria monocytogenes. Before implementation of intervention strategies, 19.2% of raw product samples (n = 276)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
65
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 37 publications
12
65
2
Order By: Relevance
“…While L. monocytogenes persistence in food processing plants and other food-associated environments has been well documented (30,33,37,38,44,47), it still remains largely unclear whether persistent strains share unique genetic or phenotypic characteristics or whether establishment of persistence is largely a random process with most L. monocytogenes strains being able to establish persistence if they are introduced into an appropriate location at an opportune time. While some authors have reported that isolates representing persistent subtypes appear to possess specific characteristics that facilitate persistence, such as resistance to disinfectants (1,39), improved ability to adhere to food contact surfaces and to form biofilms (6,40), others have found no evidence that persistent strains adhere better to surfaces (28) or are more resistant to disinfectants (14,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While L. monocytogenes persistence in food processing plants and other food-associated environments has been well documented (30,33,37,38,44,47), it still remains largely unclear whether persistent strains share unique genetic or phenotypic characteristics or whether establishment of persistence is largely a random process with most L. monocytogenes strains being able to establish persistence if they are introduced into an appropriate location at an opportune time. While some authors have reported that isolates representing persistent subtypes appear to possess specific characteristics that facilitate persistence, such as resistance to disinfectants (1,39), improved ability to adhere to food contact surfaces and to form biofilms (6,40), others have found no evidence that persistent strains adhere better to surfaces (28) or are more resistant to disinfectants (14,31).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the implementation of intensive control measures, eradication and control of L. monocytogenes in food processing environments remain considerable challenges. Several studies indicate that the most important source of food contamination with L. monocytogenes is via cross-contamination from the equipment and general environment of the processing plants, where some L. monocytogenes strains can persist over extended periods, while others are recovered only sporadically (30,33,37,38,44,47). While several authors attempted to identify specific characteristics, e.g., biofilm formation or sanitizer resistance capabilities, that may be associated with L. monocytogenes persistence in processing plants (1,6,39,49), little attention has been given to the potential contributions of prophages to the ability of L. monocytogenes to establish persistence.…”
mentioning
confidence: 99%
“…While L. monocytogenes isolates from a variety of sources (e.g., humans with clinical infections, food, and various environments) were included in this isolate set, our efforts were focused on the well-characterized set of human clinical and food isolates described by Gray et al (11). In addition to the isolates described by Gray et al (11), we selected L. monocytogenes isolates from various environments, including urban and pristine environments (34), farm environments (27), and food-processing plant environments (17). Together, the isolates from these studies constitute a combined total of 1,731 L. monocytogenes isolates representing 90 unique EcoRI ribotypes (11,17,27,34).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the isolates described by Gray et al (11), we selected L. monocytogenes isolates from various environments, including urban and pristine environments (34), farm environments (27), and food-processing plant environments (17). Together, the isolates from these studies constitute a combined total of 1,731 L. monocytogenes isolates representing 90 unique EcoRI ribotypes (11,17,27,34). Based on the frequency of ribotype occurrence, we then selected a representative subset of L. monocytogenes isolates (n ϭ 203), from which isolates belonging to ribotypes previously associated with PMSC mutations in inlA reported by Nightingale et al (26) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of sources of contamination is necessary to design intervention strategies aimed at reducing the risk of contamination (3,6,11). Often, the numbers of isolates that are genotyped in a study are based on convention, as well as limitations in time, funding, and storage capacity, rather than on a specified level of confidence about the total number of strains likely to be present in a sample.…”
mentioning
confidence: 99%